MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS III SD NEGERI DEPOK 1 MELALUI PENERAPAN MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE, SHARE) BERBANTUAN MEDIA BLOCK DIENESMODEL - Anggraeni, Romadhini Listyautami; Rahmawati, Puji; Sukmarani, Dhuta; Mulyosari, Endah Trie (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Understand mathematical concepts of class III A students at SD Negeri Depok 1 in division material. The aim of this research is to increase students' understanding of mathematical concepts in division material using the SSCS (Search, Solve, Create, and Share) model assisted by Block Dienes media. The research method used in this research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and 4 stages, namely planning, implementation, observation and reflection. The subjects of this research were 28 students in class III A of SD Negeri Depok 1, 18 male students and 10 female students. The data collection techniques used are observation and tests. Data analysis in this research uses quantitative descriptive techniques. The results of this research show that in the pre-cycle there were only 17.85% of students who had scores above the average, then in the first cycle this increased to 42.85% of students, and in the second cycle it increased again to 85.71%. Based on the research that has been carried out, it can be concluded that the use of the SSCS model assisted by block dienes media is able to increase the understanding of mathematical concepts in class III A students at SD Negeri Depok 1.